PHARMACOECONOMIC STUDY OF PRIMARY OPEN-ANGLE GLAUCOMA TREATMENT WITH FIX COMBINATION OF CARBONIC ANHYDRASE INHIBITORS AND BETABLOCKERS - M. V. Protsenko (IRBIS LLC, 2015)
Abstract: pharmacoeconomic study of treatment primary open-angle glaucoma with fix combination of carbonic anhydrise inhibitors and betablockers by mean of cost-utility, willingness-to-pay, cost minimization and budget impact analysis was conducted. Results have shown, that Azarga has benefits compare with Kosopt and combination of Azopt and timolol from cost-minimization and budget impact analysis perspective and can be claimed dominant. Futhermore Azarga in comparison with Dorzopt plus is cost-effective drug, because of Azarga incremental cost-utility ratio is lower than willingness-to-pay threshold value for Russia.